2011
DOI: 10.1007/s12015-011-9259-1
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Clinical Trials for Spinal Cord Injury: Readiness, Reluctance, Redefinition

Abstract: A wealth of scientific and clinical research has focused on the use of stem cells as a potential therapy for spinal cord injury (SCI), culminating most recently in the initiation of clinical trials. However, with the urgency that scientists and clinicians have undertaken to move forward with novel therapies for this devastating injury, the perspectives of stakeholders who live with a SCI have been left behind. Translational research in this rapidly growing field therefore overlooks a critically important viewp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…12,[14][15][16] Our results underscored the need to consider a patient's perception of risk as a dynamic rather than static phenomenon when designing clinical trials. Further research has interrogated the views of health-care professionals (HCPs) and injured individuals about the evidence needed to move from bench to bedside considering different risk frameworks.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…12,[14][15][16] Our results underscored the need to consider a patient's perception of risk as a dynamic rather than static phenomenon when designing clinical trials. Further research has interrogated the views of health-care professionals (HCPs) and injured individuals about the evidence needed to move from bench to bedside considering different risk frameworks.…”
Section: Introductionmentioning
confidence: 71%
“…9,12,[14][15][16] Definitions and meanings of risk vary, however, and understanding these in terms of hazard, exposure, consequence and probability is complex. 6 In this study, we identified three major differences in perspectives about risk between HCPs and ISCIs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, potential participants may be particularly vulnerable to hype, desperation, and the therapeutic misconception (not appreciating the diff erence between usual clinical care and research). [81][82][83] Appropriate and Equitable Access…”
Section: Innovation and Clinical Usementioning
confidence: 99%